Reducing the interfacial defect density of CZTSSe solar cells by Mn substitution. Issue 4 (4th January 2018) - Lie, Stener; Rui Tan, Joel Ming; Li, Wenjie; Leow, Shin Woei; Tay, Ying Fan; Bishop, Douglas M.; Gunawan, Oki; Wong, Lydia Helena
Abstract : Mn substitution in Cu2 Mn x Zn1− x Sn(S, Se)4 induces structural, optical and electronic property changes and reduces interfacial defects improving the device performance. Abstract : Cation disorder which arises from the size and chemical environment similarity of Cu and Zn is the limiting factor in Cu2 ZnSnS x Se4− x (CZTSSe) performance. Cation substitution is one effective way to solve this issue, however, the most commonly reported substitutes, Ag and Cd, are not ideal as they detract from the earth-abundant and non-toxic motivation of CZTSSe. Mn is a promising candidate in comparison with other candidates ( e.g. Fe, Ni or Co), because of its oxidation state stability and larger ionic size mismatch with Cu. In this study, Cu2 Mn x Zn1− x Sn(S, Se)4 (CMZTSSe) thin film solar cells were prepared by chemical spray pyrolysis and a subsequent selenization process. We study the influence of Mn substitution on the morphological, structural, optical, electrical and device properties. A distinct phase transformation from CZTSSe kesterite to C(M, Z)TSSe stannite is observed at 20% Mn substitution. A high amount of Mn substitution ( x ≥ 0.6) is shown to increase the carrier density significantly which introduces more defects and non-radiative carrier recombination as shown by quenched photoluminescence intensity. Consequently, reduction in device performance is observed for these samples. The highest power conversion efficiency is achieved at x ≈ 0.05 with η = 7.59%, V oc = 0.43 V, J sc = 28.9 mA cm −2 and FF = 61.03%. The improved open circuit voltage ( V oc ) and fill factor (FF) are attributed to the improved shunt resistance and carrier transport due to low defect density especially at the CdS/CMZTSSe interface. Finally, based on our electrical characterization, a few suggestions to improve the efficiency are proposed.